Claudin-5 is involved in breast cancer cell motility through the N-WASP and ROCK signalling pathways - Escudero-Esparza Astrid; Jiang Wen G; Martin Tracey A (Journal of Experimental & Clinical Cancer Research, 2012)
Abstract Background Recent studies have shown dysregulation in TJ structure of several cancers including breast. Claudin-5 is a protein member of the TJ structure expressed in both endothelial and epithelial cells. This study examined the level of expression and distribution of Claudin-5 in human breast cancer tissues and the effect of knockdown and forced expression of Claudin-5 in the MDA-MB-231 breast cancer cell line. Methods Immunohistochemistry and quantitative-PCR were used to analyse patient tissue samples. The Claudin-5 gene was cloned and overexpressed or knocked down using ribozyme technology in human breast cancer cells. Changes in function were assessed using in vitro assays for invasion, growth, adhesion, wounding, motility, transepithelial resistance and electric cell-substrate impedance sensing. Changes in cell behaviour were achieved through the use of Hepatocyte Growth factor (HGF) which we have shown to affect TJ function and expression of TJ proteins. In addition, an in vivo model was used for tumour growth assays. Results data was analyzed using a Students two sample t-test and by Two-way Anova test when the data was found to be normalized and have equal variances. In all cases 95% confidence intervals were used. Results Patients whose tumours expressed high levels of Claudin-5 had shorter survival than those with low levels (p = 0.004). Investigating in vitro the effect of altering levels of expression of Claudin-5 in MDA-MB-231cells revealed that the insertion of Claudin-5 gene resulted in significantly more motile cells (p < 0.005). Low levels of Claudin-5 resulted in a decrease in adhesion to matrix (p < 0.001). Furthermore, a possible link between Claudin-5 and N-WASP, and Claudin-5 and ROCK was demonstrated when interactions between these proteins were seen in the cells. Moreover, followed by treatment of N-WASP inhibitor (Wiskostatin) and ROCK inhibitor (Y-27632) cell motility was assessed in response to the inhibitors. Results showed that the knockdown of Claudin-5 in MDA-MB-231 masked their response after treatment with N-WASP inhibitor; however treatment with ROCK inhibitor did not reveal any differences in motility in this cell line. Conclusions This study portrays a very new and interesting role for Claudin-5 in cell motility involving the N-WASP signalling cascade indicating a possible role for Claudin-5 in the metastasis of human breast cancer.